Chatbot-delivered structured psychological intervention (SPI-Bot) for teenagers with adolescent idiopathic scoliosis in Hong Kong: protocol for a pilot randomised controlled trial - Yan Li; Jiaying Li; Engle Angela Chan; Teng Zhang; Yuan Cao; Nan Meng; Lu Yu; Jason Pui Yin Cheung; Zhaolong Wu; Dennis Chak Fai Ma (BMJ Open)
Introduction Adolescent idiopathic scoliosis (AIS) often imposes a significant psychological burden on teenagers. Cognitive and behavioural strategies have demonstrated the potential to alleviate these challenges. Chatbots, with their real-time interaction capabilities, provide a promising and accessible approach to delivering psychological interventions for young people.Method and analysis This pilot trial will evaluate a chatbot-delivered, structured psychological intervention (SPI-Bot) incorporating cognitive and behavioural strategies for teenagers with AIS. Conducted as a single-centre, parallel-group randomised controlled trial, the study aims to assess the feasibility, acceptability and preliminary effectiveness of SPI-Bot. Fifty-two teenagers with AIS and mild to moderate psychological symptoms will be block-randomised into two groups. The intervention group will complete an 8-week, evidence-based SPI-Bot programme, while the control group will engage in casual conversations with another chatbot that does not include specific psychological health content. Assessments will be conducted at baseline, postintervention (8 weeks) and follow-up (12 weeks). Primary outcomes include feasibility and acceptability, measured through recruitment rates, adherence rates, attrition rates, engagement, working alliance, usability, user experience and adverse events. Secondary outcomes focus on effectiveness, including psychological distress, psychological well-being, perceived social support and quality of life. Participants in the intervention group will be purposively sampled for semistructured interviews to explore their perceptions of the intervention process.Ethics and dissemination This study has been approved by the Institutional Review Board of the Hong Kong Polytechnic University (Reference: HSEARS20240919007). The results of this pilot study will be disseminated through peer-reviewed journals and conference presentations.Trial registration number NCT06698952